Clonal evolution of CD8+ T cell responses against latent viruses: relationship among phenotype, localization, and function - Remmerswaal, EB (2015)
Human cytomegalovirus (hCMV) infection is characterized by a vast expansion of resting effector-type virus-specific T cells in the circulation. In mice, interleukin-7 receptor α (IL-7Rα)-expressing cells contain the precursors for long-lived antigen-experienced CD8(+) T cells, but it is unclear if similar mechanisms operate to maintain these pools in humans. Here, we studied whether IL-7Rα-expressing cells obtained from peripheral blood (PB) or lymph nodes (LNs) sustain the circulating effector-type hCMV-specific pool. Using flow cytometry and functional assays, we found that the IL-7Rα(+) hCMV-specific T cell population comprises cells that have a memory phenotype and lack effector features. We used next-generation sequencing of the T cell receptor to compare the clonal repertoires of IL-7Rα(+) and IL-7Rα(-) subsets. We observed limited overlap of clones between these subsets during acute infection and after 1 year. When we compared the hCMV-specific repertoire between PB and paired LNs, we found many identical clones but also clones that were exclusively found in either compartment. New clones that were found in PB during antigenic recall were only rarely identical to the unique LN clones. Thus, although PB IL-7Rα-expressing and LN hCMV-specific CD8(+) T cells show typical traits of memory-type cells, these populations do not seem to contain the precursors for the novel hCMV-specific CD8(+) T cell pool during latency or upon antigen recall. IL-7Rα(+) PB and LN hCMV-specific memory cells form separate virus-specific compartments, and precursors for these novel PB hCMV-specific CD8(+) effector-type T cells are possibly located in other secondary lymphoid tissues or are being recruited from the naive CD8(+) T cell pool. IMPORTANCE: Insight into the self-renewal properties of long-lived memory CD8(+) T cells and their location is crucial for the development of both passive and active vaccination strategies. Human CMV infection is characterized by a vast expansion of resting effector-type cells. It is, however, not known how this population is maintained. We here investigated two possible compartments for effector-type cell precursors: circulating acute-phase IL-7Rα-expressing hCMV-specific CD8(+) T cells and lymph node (LN)-residing hCMV-specific (central) memory cells. We show that new clones that appear after primary hCMV infection or during hCMV reactivation seldom originate from either compartment. Thus, although identical clones may be maintained by either memory population, the precursors of the novel clones are probably located in other (secondary) lymphoid tissues or are recruited from the naive CD8(+) T cell pool.